2013
DOI: 10.2967/jnumed.112.105379
|View full text |Cite
|
Sign up to set email alerts
|

Nigrostriatal Dopamine Terminal Imaging with Dopamine Transporter SPECT: An Update

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to describe (1) the radiopharmaceuticals used to evaluate nigrostriatal dopamine imaging; (2) the pattern of uptake of these radiopharmaceuticals in parkinsonian syndromes; and (3) the role of these radiopharmaceuticals in the evaluation of parkinsonian syndromes.Financial Disclosure: Dr. Tatsch is a meeting participant/lecturer for GE Healthcare. The authors of this article have indicated no other relevant relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 76 publications
3
62
0
6
Order By: Relevance
“…Results: Raw striatal intensities and SBR values presented significant differences across distinct camera models. We demonstrate that GCDF normalization efficiently alleviated these differences in striatal quantification and with values constrained to a fixed interval [0,1]. Also, our method allowed a fully automated image assessment that provided maximal classification ability, given by an area under the curve (AUC) of AUC = 0.94 when used mean regional variables and AUC = 0.98 when used voxel-based variables.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results: Raw striatal intensities and SBR values presented significant differences across distinct camera models. We demonstrate that GCDF normalization efficiently alleviated these differences in striatal quantification and with values constrained to a fixed interval [0,1]. Also, our method allowed a fully automated image assessment that provided maximal classification ability, given by an area under the curve (AUC) of AUC = 0.94 when used mean regional variables and AUC = 0.98 when used voxel-based variables.…”
Section: Introductionmentioning
confidence: 99%
“…Then, as a proof-of-concept example, we evaluate the performance of a binary classifier based on logistic regression to distinguish between healthy controls and PD after GCDF normalization when images from multiple sites were pooled together. As a reference, previous single-center studies have demonstrated that the diagnostic accuracy of visual expert reading or SBR-based classifiers can be as high as of 95 % [1,4]. We evaluated a low dimensional classifier using striatal ROI variables (bilateral putamen and caudate) and also a higher dimensional one using all striatal voxels; in both cases we used a logistic regression classifier and tenfold cross-validation for evaluation.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Low dopamine transporter uptake in basal ganglia demonstrated by SPECT or PET imaging is the only imaging feature in the diagnostic criteria for LBD [79] . However, FP-CIT SPECT is not indicated to distinguish between different parkinsonian syndromes [93] . FP-CIT SPECT scan has a sensitivity of 78% and a specificity of 90% with an overall accuracy of 80% to distinguish between normal (or AD) and a parkinsonian syndrome (LBD) [94] .…”
Section: Molecular Imagingmentioning
confidence: 99%